Impact evaluation of a social protection programme paired with fee waivers on enrolment in Ghana’s National Health Insurance Scheme - Tia M Palermo; Clare Barrington; Elsa Valli; Gustavo Ángeles-Tagliaferro; Marlous de Milliano; Clement Adamba; Tayllor Renee Spadafora; Tia Palermo; Richard de Groot; Isaac Osei-Akoto; Joseph K. Darko; Robert Darko Osei; et al. (BMJ Open)
Objectives The study aimed to understand the impact of integrating a fee waiver for the National Health Insurance Scheme (NHIS) with Ghana’s Livelihood Empowerment Against Poverty (LEAP) 1000 cash transfer programme on health insurance enrolment.Setting The study was conducted in five districts implementing Ghana’s LEAP 1000 programme in Northern and Upper East Regions.Participants Women, from LEAP households, who were pregnant or had a child under 1 year and who participated in baseline and 24-month surveys (2497) participated in the study.Intervention LEAP provides bimonthly cash payments combined with a premium waiver for enrolment in NHIS to extremely poor households with orphans and vulnerable children, elderly with no productive capacity and persons with severe disability. LEAP 1000, the focus of the current evaluation, expanded eligibility in 2015 to those households with a pregnant woman or child under the age of 12 months. Over the course of the study, households received 13 payments.Primary and secondary outcome measures Primary outcomes included current and ever enrolment in NHIS. Secondary outcomes include reasons for not enrolling in NHIS. We conducted a mixed-methods impact evaluation using a quasi-experimental design and estimated intent-to-treat impacts on health insurance enrolment among children and adults. Longitudinal qualitative interviews were conducted with an embedded cohort of 20 women and analysed using systematic thematic coding.Results Current enrolment increased among the treatment group from 37.4% to 46.6% (n=5523) and decreased among the comparison group from 37.3% to 33.3% (n=4804), resulting in programme impacts of 14 (95% CI 7.8 to 20.5) to 15 (95% CI 10.6 to 18.5) percentage points for current NHIS enrolment. Common reasons for not enrolling were fees and travel.Conclusion While impacts on NHIS enrolment were significant, gaps remain to maximise the potential of integrated programming. NHIS and LEAP could be better streamlined to ensure poor households fully benefit from both services, in a further step towards integrated social protection.Trial registration number RIDIE-STUDY-ID-55942496d53af.